Applying the Concept of Trust in Managing breach of ethics and integrity in Malaysia: constructive trust as the best possible remedy - Ali, Zuraidah (Eubios Ethics Institute, 2010)
Ethics and integrity have always been associated with individual personality and honesty and these wide concepts are applicable in all kinds of situation. Trust, on the other hand, is also closely related to integrity. In order for trust to be established, a trustee needs to be appointed, and the highest form of integrity is expected from a trustee whereby the property that he is holding, as a legal owner, is not his but it belongs to a beneficiary or beneficiaries. Similarly, in cases involving charitable trust, trustees need to be aware that trust funds in most cases donated by the public are well managed. In principle, if it is used for other purposes set by such trust; this will eventually lead to breach of trust. Conversely in a case where it does not involve any direct creation of trust and appointment of trustee, the element of fraud and malpractice in managing any affairs may give rise to breach of trust by which court may interfere by invoking the concept of constructive trust as a legal remedy. The attitude of the courts in Malaysia in recognizing rights arising directly or sometimes indirectly from trust has been very clear, but the issue as to whether remedies for breach of trust is the best method in dealing with breach of ethics and integrity needs to be examined. This paper looks at possible legal remedies available in dealing with breach of ethics and integrity especially at workplace and also at other possible circumstances involving social relationships. It also examines the current situation dealing with charitable organization in coming to the conclusion as to whether there is a need for a proper monitoring mechanism in ensuring that public fund is properly utilized. The methodology used are statutory and case law analysis.